Decadal shifts in sediment dynamics and organic matter accumulation in a highly anthropogenic tropical bay: Banten Bay, Indonesia - Nur Aziza; Dietriech Geoffrey Bengen; Tri Prartono; Rastina Rastina (Universitas Malikussaleh, 2026)
Banten Bay is a semi-enclosed coastal system subjected to intensifying environmental pressures from anthropogenic activities and fluvial inputs, rendering it highly susceptible to alterations in sediment characteristics and organic matter accumulation. This study aims to analyze the distribution of sediment and organic matter content at five strategic observation stations in the waters of Banten Bay. Sediment fraction analysis was conducted using the standard sieving method (ASTM D422-63), while organic matter content was quantified via the Loss on Ignition (LOI) technique. The results reveal that the sediment is predominated by fine-grained particles, specifically silt (64.39 – 76.41%) and clay (21.96 – 27.47%), whereas the sand fraction represents the lowest proportion (1.26 – 9.87%). Based on the USDA textural classification, the sediment is categorized as silty clay. Organic matter content varied between 6.267% and 12.067%, with the highest concentrations observed at central bay stations and those adjacent to mangrove ecosystems. The spatial distribution of fine sediments and organic matter is intrinsically linked to local hydrodynamics, where low-energy current environments facilitate the deposition and retention of fine particles. These findings indicate that Banten Bay’s current environmental regime promotes high fine-sediment deposition and organic matter accumulation, reflecting a significant shift in environmental dynamics compared to historical conditions. This study provides essential baseline data for environmental quality management and long-term ecosystem monitoring in Banten Bay. Keywords: Anthropogenic Pressure; Banten Bay; Organic Matter; Hydrodynamics; Sediment Grain